DETERMINATION THE QUALITY OF DRINKING WATER BY INDIRECT METHOD ON SCALE TEST - B. Rajković, M.; Tomić, Z.; D. Stojanović, M.; Đorđević, A.; M. Sudar, M. (Journal of Engineering & Processing Management, 2010)
Investigation of the composition of elements in drinking water, from water network of Belgrade city, with indirect method. This method is based on the scale that is made with precipitation from the water during heating, indicated presence of alkali and alkaline earth elements to a greater extent and heavy metals which is quite expected. Somewhat unexpectedly the presence of some elements, whose presence leads to a greater amount isn’t desirable, because they have the cumulative effect (Hg, Pb, Ni, As ), which indicates that these are areas of developed industrial production. The water from which was formed scale found a greater presence of Fe, Cu, and Mn. Scale testing determined the presence of radioactive elements U and Sr in drinking water. Based on X-ray diffraction analysis of the composition of the sample is composed of a mixture Mg calcite and aragonite. Multidisciplinary approach to the analysis of the scale is defining the new original indirect method of determining the quality of drinking water, so far not recorded in the literature.